2016
DOI: 10.1111/jdv.13642
|View full text |Cite
|
Sign up to set email alerts
|

The hair grooming practices of women of African descent in London, United Kingdom: findings of a cross‐sectional study

Abstract: The hair-care practices of women of African descent should be borne in mind when treating hair and scalp disorders in this group. Although the current trend is towards natural hairstyles, some adverse hair-care practices still persist which should be addressed through culturally appropriate public health messages on hair loss prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Once braided, braids usually remain intact for several weeks or months and may be washed less frequently, causing scalp dirt build up and inflammatory conditions [23]. A study including 242 women of African descent reported that on average, braid or weave hairstyles are worn for 63 days (range 56.3‐69.7) [24]. In the same study, it was also observed that the time between hair washes ranged from 18 to 32 days.…”
Section: Introductionmentioning
confidence: 99%
“…Once braided, braids usually remain intact for several weeks or months and may be washed less frequently, causing scalp dirt build up and inflammatory conditions [23]. A study including 242 women of African descent reported that on average, braid or weave hairstyles are worn for 63 days (range 56.3‐69.7) [24]. In the same study, it was also observed that the time between hair washes ranged from 18 to 32 days.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are supported by the work of Dadzie et al who found an average of two straightening per 88 days. 27 44.8% often/always had burns after straightening. This result could indicate noncompliance or ignorance of hair straightening instructions by providers of this service.…”
Section: Discussionmentioning
confidence: 97%
“…25,26 However, hair straightening has been labelled as one of the factors involved in the onset of TA. 27 Nearly half participants (43.9%) straightened their hair twice or thrice a year. Our results are supported by the work of Dadzie et al who found an average of two straightening per 88 days.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations